ChemInform Abstract: Emerging Role of Room Temperature Ionic Liquids (RTILs) in Carbohydrate Chemistry. Issue 16 (22nd April 2014) - Prasad, Virendra; Kushwaha, Divya; Mishra, Kunj B.; Mishra, Lallan; Tiwari, Vinod K.
Abstract Review: 133 refs.